2013
DOI: 10.1614/wt-d-12-00167.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Weed Management Practices and Problem Weeds in the Midsouth United States—Soybean: A Consultant's Perspective

Abstract: Th is report explores the impact of the adoption of genetically engineered (GE) corn, soybean, and cotton on pesticide use in the United States, drawing principally on data from the United States Department of Agriculture. Th e most striking fi nding is that GE crops have been responsible for an increase of 383 million pounds of herbicide use in the U.S. over the fi rst 13 years of commercial use of GE crops (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008).Th is dramatic increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(110 citation statements)
references
References 40 publications
4
105
0
1
Order By: Relevance
“…This result confirmed that the RS soybean producers prefer to use this technology, being that the adoption of this technology can be attributed to the fact of the simplicity and flexibility of the use of the herbicide (Riar et al, 2013b). Thus, for the most part, RS farmers use glyphosate consecutively as the only herbicide for RR ® crops, in some cases for up to nine years (Ulguim et al, 2013).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…This result confirmed that the RS soybean producers prefer to use this technology, being that the adoption of this technology can be attributed to the fact of the simplicity and flexibility of the use of the herbicide (Riar et al, 2013b). Thus, for the most part, RS farmers use glyphosate consecutively as the only herbicide for RR ® crops, in some cases for up to nine years (Ulguim et al, 2013).…”
Section: Resultssupporting
confidence: 67%
“…To this end, we observed in this study that the vast majority (90%) of the producers use herbicides associated with glyphosate in pre-sowing soybean desiccation ( Figure 5). In 61% of the RR ® soybean crop area in the South Central Region of the United States, an additional herbicide was used in the pre-sowing application of the crop, followed by glyphosate applications in post-emergence (Riar et al, 2013b). In comparison, between 2005 and 2010, most producers have introduced in their management systems the combination of additional herbicides and glyphosate in continuously cultivated areas with RR ® soybean (Prince et al, 2012), due to the increasing problems related to weed resistance to glyphosate.…”
Section: Continued Use Of Rrmentioning
confidence: 99%
“…Weed management is an important component of soybean production to secure higher yields (Norsworthy 2003). Application of pre-emergence (PRE) and/or postemergence (POST) herbicides is the primary method for weed control in soybean (Riar et al 2013). The acetamides are widely used in corn, cotton (Gossypium hirsutum L.), sorghum [Sorghum bicolor (L.) Moench], and soybean for control of annual grasses and smallseeded broadleaf weeds.…”
mentioning
confidence: 99%
“…Miller and Norsworthy [120] reported that the addition of a residual herbicide, such as trifluralin, would provide an additional effective herbicide mode of action for managing resistant Palmer amaranth. Applications of 2,4-D, glyphosate, and glufosinate alone or tankmixed represent broad-spectrum POST herbicides that have the potential to control 9 of the 10 most problematic weeds in the southern cotton and soybean production [121].…”
Section: High Plains Studiesmentioning
confidence: 99%